2018
DOI: 10.3390/su11010158
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms and Entrepreneurial Action: The Mediating Role of Opportunity Confidence

Abstract: The aim of this paper is to investigate the mediating effect of opportunity confidence (OC) on the relationship between social norms (SNs) and decision to engage in entrepreneurial action (EA). The sample size includes prospective entrepreneurs engaged in the field of Information and Communications Technology (ICT) in science and technology parks in Iran. This research uses the longitudinal survey method. Research findings from the structural equation modeling (SEM) do not confirm the mediating role of OC. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 98 publications
3
32
0
Order By: Relevance
“…Entrepreneurial opportunity is the formation of new means, new goals, or new means-goals to achieve the possibility of introducing new products, new services, new raw materials, and new ways of an organization [1]. At the same time, from a sustainable perspective, some scholars found that identifying, evaluating, and developing sustainable entrepreneurial opportunities can improve the ecological and social environment, and obtain economic returns while eliminating market failure related to ecological and social problems [23][24][25].…”
Section: Entrepreneurial Opportunities Identificationmentioning
confidence: 99%
“…Entrepreneurial opportunity is the formation of new means, new goals, or new means-goals to achieve the possibility of introducing new products, new services, new raw materials, and new ways of an organization [1]. At the same time, from a sustainable perspective, some scholars found that identifying, evaluating, and developing sustainable entrepreneurial opportunities can improve the ecological and social environment, and obtain economic returns while eliminating market failure related to ecological and social problems [23][24][25].…”
Section: Entrepreneurial Opportunities Identificationmentioning
confidence: 99%
“…Most authors introduced their understanding of this process based on fields of study such as organization theory, services marketing, strategic management, innovation, media, and communications management [96][97][98][99][100][101]. Researchers mainly surveyed value co-creation based on Business to Customer (B2C) and Business to Business (B2B) themes [44,[102][103][104]. They analyzed the final customer's involvement in activities such as product designing, manufacturing, assembling, transporting, and maintaining [28,105].…”
Section: Value Co-creation Framework and Modelsmentioning
confidence: 99%
“…So, we have a contradiction, between the global tax revenue and the costs of companies (Kuhn, 1962;Salamzadeh et al, 2017;Batrancea et al, 2019). Then, the conclusion is that temporarily the increasing costs decrease the money deposit of the companies, but finally the will have much more profits (Boland, 1991;Rein and Schon, 1993;Hallerberg and Bassinger, 1998;Ariely et al, 2003;Khajeheian et al, 2018; Salamzadeh, 2018; Emami and Khajeheian, 2019). Contemporaneously, the tax authorities should try to reduce the costs of the companies or to make it cheaper, to achieve more tax income for the tax revenue (King, 1984;Hoynes, 1996;Camerer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Journal ofEntrepreneurship, Business, and Economics, 2020, 8(1),[1][2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%